2013
DOI: 10.1016/j.earlhumdev.2013.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Non-contact heart rate monitoring utilizing camera photoplethysmography in the neonatal intensive care unit — A pilot study

Abstract: Contactless heart rate monitoring by means of a camera using ambient light was demonstrated for the first time in the NICU population and appears feasible. Better hardware and improved algorithms are required to increase robustness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
162
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(176 citation statements)
references
References 14 publications
0
162
0
Order By: Relevance
“…However, their system was outperformed by camerabased PPG measurements in some cases and is likely to be susceptible to noise due to rigid head motions. A pilot study in infant monitoring has demonstrated accurate measurement of HR using remote PPG measurements from a camera in realistic conditions [1], HRV measurements were not validated.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their system was outperformed by camerabased PPG measurements in some cases and is likely to be susceptible to noise due to rigid head motions. A pilot study in infant monitoring has demonstrated accurate measurement of HR using remote PPG measurements from a camera in realistic conditions [1], HRV measurements were not validated.…”
Section: Related Workmentioning
confidence: 99%
“…Applications that would benefit from non-contact measurement of heart rate (HR) and heart rate variability (HRV) include: infant monitoring [1], detection of cardiac diseases [2] and stress monitoring [3]. The current gold standard methods of measuring HR and HRV involve obtrusive devices attached to the body, in some cases requiring sticky gels and/or uncomfortable electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…The first medical study of camera-based pulse rate monitoring for neonates was reported by Scalise et al [4]. However, they recorded the infants only in supine positions together with a non-ambient green light source (green channel shows the strongest pulse signal [8]).…”
Section: Current Trendsmentioning
confidence: 99%
“…However, they recorded the infants only in supine positions together with a non-ambient green light source (green channel shows the strongest pulse signal [8]). The first to include ambient light conditions in a medical study was Aarts et al [4]. They explored different scenes with challenging conditions for 19 infants in durations of 1 to 5 mins.…”
Section: Current Trendsmentioning
confidence: 99%
See 1 more Smart Citation